Efforts in Hypercholesterolemia Treatment Using Turmeric (Curcuminoid) Extract Phytotherapy on Obese Patients: Preclinical Study - Galih Jatnika; Susilawati Hartanto (Jurnal Keperawatan Padjadjaran, 2018)
Hypercholesterolemia is an escalation in total cholesterol levels in the blood which can cause various cardiovascular diseases, hypertension, and stroke. Obesity is one of the risk factors of hypercholesterolemia. Turmeric extract (a curcuminoid) therapy including phytotherapy can be used to overcome hypercholesterolemia. This research aims to identify hypercholesterolemia with turmeric extract for obesity patients. The method used in this research was quasi-experimental with one group pretest and posttest design. The sampling technique used in this research was purposive sampling. The research subjects consisted of 18 respondents who met the criteria of hypercholesterolemia (total cholesterol> 200 mg/dl) or with obesity who had a body mass index (BMI)> 25 kg /m²) and they were not taking cholesterol-lowering drugs. Subjects were given turmeric extract with a dose of 1 gram/day for 28 days. Before and after the intervention, total cholesterol levels of respondents were examined. Data analysis was done by using t-paired test. The results showed that the average total cholesterol level before the patient was given turmeric extract therapy was 234.44 mg/dl and 202.06 mg/dl after the treatment. There was a significant decrease in the average cholesterol level after they were given turmeric extract therapy with p-value 0.0001 (ɑ <0.05). The results showed that there was a significant decrease in cholesterol levels, although it was still included in the category of borderline high cholesterol levels. Researchers suggest that respondents continue their turmeric extract therapy with a low cholesterol diet until their total cholesterol levels achieve the normal state.